Blended multiple modeling of non-linear systems - Lin, Thurein. (2008)
We explain the control system theory background, characteristics of control system and its requirements. Then, linear control system and nonlinear control system also described here. We also emphasize on the modeling of nonlinear control systems and its linearization. We elaborate the nonlinear dynamic system with the suitable example and make simulation with different parameters. We use the different control laws and compare the output result of each control law.